ANALISA KUALITAS HASIL PRODUK PADA PENGERJAAN POCKETING DENGAN MESIN CNC FRAIS 3 AXIS - Irfan Santosa; Siswiyanti Siswiyanti; Muhammad Nur Alif (Jurnal Teknologi Terapan, 2021)
The manufacturing industry sector is experiencing increasing development. Especially CNC-based machines and the demands of consumers who want good workpiece quality, precision/accuracy of workpiece dimensions and roughness values are the main elements in the machining process. This study uses an experimental method, namely to determine the quality of the product (dimensions, time, geometry and roughness of the workpiece) in pocket work using a 3 axis CNC Milling Microcontroller Match 3 machine for the manufacture of aluminum ashtray products. For the parameters used, it uses a cutting speed of 150 mm/minute, a cutting depth of 0.5 mm with a Spindle rotation speed of 10,000 RPM. The results of this study can be seen in the aluminum ashtray product, the processing time is 1098 minutes, while the dimensions of the workpiece have an average tolerance of 0.28 mm and for the average roughness value N7 = 2.1 µm and it can be classified that the quality of the products made by the CNC Milling Machine 3 axis Microcontroller Match 3 in standard category for tolerance category and roughness value.